(untitled) - Wheelon, Albert Dewell (Cambridge UK, 2001)
Electromagnetic Scintillation describes the phase and amplitude fluctuations imposed on signals that travel through the atmosphere. The two volumes of Electromagnetic Scintillation will constitute a modern reference and comprehensive tutorial, treating both optical and microwave propagation and integrating measurements and predictions at each step of the development. This first volume deals with phase and angle-of-arrival measurement errors, accurately described by geometrical optics and will be followed by a second volume on weak scattering. In this book, measured properties of tropospheric and ionsopheric irregularities are reviewed first. Electromagnetic fluctuations induced by these irregularities are then estimated for a wide range of applications.
Keywords: Electromagnetic waves,Bức xạ điện từ; Transmission